MANFAAT HASIL PELATIHAN MANIPULATING FABRIC SEBAGAI KESIAPAN MEMBUKA USAHA AKSESORIS - Fedix Nanda Devy Pertiwi; Marlina Marlina (Fesyen Perspektif, 2015)
Manipulating Fabric training Internship Program conducted at the Quenta Training Course with a purpose to preparing student when returning to the society so it can creating an accessories business. This research aims to obtain data on the advantages of Manipulating Fabric training results as readiness to open an accessories business in terms of mastering the basic concepts of manipulating fabric, manipulating fabric product design, material selection of textiles knowledge, tools, and garnitur manipulating fabric manufacture, and manipulatin fabric manufacture with basic techniques of gathering and pleat after Manipulating Fabric training. The research method used descriptive method with data collection tools in the form of a questionnaire. The samples used a total sample directed to 22 people of Madrasah Aliyah Negeri 1 Bandung, Tata Busana skill class XII of 2011 and 2012 which follows the Internship Program. The results showed generally more than half of student have benefited from Manipulating Fabric training results as readiness to open an accessories business. The findings from this study that the results need to be applied in Manipulating Fabric training to open an accessories business. The conclusion from this study that the results of Manipulating Fabric training is have a great benefit to the students so they are ready to open an accessories business.